Integration of Virtual Reality to Preserve Nigeria’s Cultural Heritage Using Technology Acceptance Model and Constructivism Learning Theory - Esan, Omobayo (Fountain of Informatics Journal, 2025)
Abstract Nigeria's cultural heritage, encompassing rich traditions, historical landmarks, and intangible practices, faces threats from urbanization, globalization, and inadequate preservation efforts. Virtual Reality (VR) offers an innovative solution for documenting, preserving, and promoting this heritage by creating immersive and interactive experiences. This paper explores the application of VR in preserving Nigeria's tangible and intangible cultural heritage, including oral traditions, traditional festivals, and historical landmarks like the Sukur Cultural Landscape and Osun-Osogbo Sacred Grove. While VR has gained traction globally in cultural heritage preservation, its adoption in Nigeria remains limited due to challenges such as high costs, limited accessibility, and lack of localized content. By addressing these gaps, VR can enhance cultural awareness, engage younger generations, and boost cultural tourism. This study highlights existing works in VR applications for cultural preservation globally and identifies opportunities for tailored VR solutions in the Nigerian context. The findings emphasize the importance of collaborative approaches involving technologists, researchers, and cultural custodians to ensure effective VR integration. Ultimately, the study advocates for leveraging VR to safeguard Nigeria’s cultural legacy, offering innovative pathways to promote its heritage on a global scale while ensuring intergenerational continuity. Keywords: virtual reality (VR), technological acceptance model, constructivism learning theory, cultural heritage